The Correlations Between Premature Rupture of Membranes and Gestational Age with The Incidence of Asphyxia Neonatorum - Rina Apriliani; Elisa Ulfiana; Ngadiyono Ngadiyono (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2021)
PROM was one of the factors causing asphyxia neonatorum, oligohydramnios can caused retroplacenter circulation disorders. Other risk factor are preterm delivery and posterm delivery. A dangerous threat to preterm babies is difficulty in breathing because the lungs and respiratory system have not work perfectly. This research to determine the correlations between premature rupture of membranes and gestational age with the incidence of asphyxia neonatorum in the maternal room of KRT Setjonegoro Wonosobo Hospital. This research was an analysis correlations with an observational design and using a retrospective approach. The sample was newborn babies as many as 184 respondents with a simple random sampling technique. The data analysis methods in this research used the Chi-Square test. The results of bivariate analysis between premature rupture of membranes and the incidence of asphyxia neonatorum showed a ρ value of 0,000, gestational age with the incidence of asphyxia neonatorum showed a ρ value of 0,000. There is a correlations between premature rupture of membranes and gestational age with the incidence of asphyxia neonatorum. It was recommended for pregnant women to be active in seeking information about the impact of asphyxia. Researcher expected to always increase knowledge about PROM, preterm and posterm pregnancy.